DESAIN REAKTOR TRANSESTERIFIKASI PADA PRAPERANCANGAN PABRIK METIL ESTER DARI CPO (CRUDE PALM OIL) - Idral Amri; Tifanny Frimacia (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
Along with the development of the era, the need for fuel oil is increasing. The development of research and the use of diesel motors in industry will not stop just because of the depletion of fossil fuels. The search for alternative fuels as a substitute for diesel continues to be carried out in addition to dealing with the problems of the global energy and environmental crisis as well as helping to develop automotive technology as a work of human culture. Methyl ester is a biofuel that can be used to power diesel engines. The availability of fuel oil derived from petroleum is running low and the price is increasing so that alternative fuel sources are needed. One of the substitutes for conventional fuels from petroleum is vegetable oil. Methyl ester is produced using a transesterification reaction by changing the triglycerides which are reacted with one of the alcohol compounds, namely methanol to become methyl ester, and a production capacity of 250,000 tons / year is obtained. The main design tool is the CSTR (Continuous Flow Stirred-Tank Reactor) reactor which is used as a place for the transesterification reaction between triglycerides and methanol to produce methyl ester (main product) and glycerol (by-product). The operating temperature used is 333.15K. Based on the calculation results, the reactor volume is 57.28 m3, the reactor diameter (OD) is 168 in m with torispherical flanged and dished head and skirt support.